Lithium treatment and cancer incidence in bipolar disorder. (16th February 2016) - Martinsson, Lina; Westman, Jeanette; Hällgren, Jonas; Ösby, Urban; Backlund, Lena
Abstract : Objectives: To investigate whether there is an increased risk of cancer associated with lithium treatment in patients with bipolar disorder compared to the general population. Methods: A nationwide Swedish register study of incidence rate ratios (IRRs) of total cancer and site‐specific cancer in the 50–84‐year age range was carried out in patients with bipolar disorder (n = 5, 442) with and without lithium treatment from July 2005 to December 2009 compared to the general population using linked information from The Swedish Cancer Register, The National Patient Register, and The Drug Prescription Register. Results: The overall cancer risk was not increased in patients with bipolar disorder. There was no difference in risk of unspecified cancer, neither in patients with lithium treatment compared to the general population [IRR = 1.04, 95% confidence interval (CI): 0.89–1.23] nor in patients with bipolar disorder without lithium treatment compared to the general population (IRR = 1.03, 95% CI: 0.89–1.19). The cancer risk was significantly increased in patients with bipolar disorder without lithium treatment in the digestive organs (IRR = 1.47, 95% CI: 1.12–1.93), in the respiratory system and intrathoracic organs (IRR = 1.72, 95% CI: 1.11–2.66), and in the endocrine glands and related structures (IRR = 2.60, 95% CI: 1.24–5.47), but in patients with bipolar disorder with lithium treatment, there was no significantly increased cancer risk compared to the general population. Conclusions: Bipolar disorder was not associated with increased cancer incidence and neither was lithium treatment in these patients. Specifically, there was an increased risk of respiratory, gastrointestinal, and endocrine cancer in patients with bipolar disorder without lithium treatment.